Asymmetric polymer materials: Synthesis, structure, and performance. (1st March 2022) - Hnatchuk, Nataliia; Pawale, Tejal; Li, Xiao
Abstract: The asymmetric structure is the natural part of the environment and can be found in many biological systems. The irregularity in the materials morphology or functionality often led to the performance enhancement in comparison to the isotropic material, such as selectivity, permeability, stability, transport mechanism, mechanic resistance, etc. Usually those systems exhibit the distinct adaptability bringing them to the intelligent materials category. In this review the various asymmetric structures have been highlighted together with their synthesized approaches: top-down (lithography, etching, electrospinning, 3D/4D printing), bottom-up (phase inversion, blending) and synthetic (layering, confinement). Additionally, the current and potential applications in the medical, biological, engineering, electronics and optical fields have been featured. Graphical abstract: Image 1